Strategi Komunikasi Pemasaran Dakwah dalam Zakat BAZNAS pada Awal Pandemi Covid-19 - Erdin Sumardianto (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
Effective marketing of zakat da'wah is urgently needed in Indonesia's early days of the Covid-19 pandemic, which resulted in a global economic recession. This study aims to describe the implementation of the da'wah zakat marketing communication strategy implemented by BAZNAS in the early days of the pandemic. The research approach uses descriptive qualitative, which collects data from various relevant sources. The theory used is Philip Kotler's Marketing Communication Theory. The results of the research show that BAZNAS's marketing communication strategy is as follows: the target market is individual muzzaki, government agencies and representatives of foreign countries; the promotion objective is to influence and motivate muzzaki to give zakat during a pandemic; the design of the message touches on the rational, emotional and moral side of muzzaki with the theme